2021
DOI: 10.1007/s00259-021-05269-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preclinical evaluation of [11C]MTP38 as a novel PET ligand for phosphodiesterase 7 in the brain

Abstract: Purpose Phosphodiesterase (PDE) 7 is a potential therapeutic target for neurological and inflammatory diseases, although in vivo visualization of PDE7 has not been successful. In this study, we aimed to develop [11C]MTP38 as a novel positron emission tomography (PET) ligand for PDE7. Methods [11C]MTP38 was radiosynthesized by 11C-cyanation of a bromo precursor with [11C]HCN. PET scans of rat and rhesus monkey brains and in vitro autoradiography of brain se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…We recently developed 11 C‐labeled MTP38 ([ 11 C]MTP38) as a positron emission tomography (PET) tracer for the imaging of PDE7 (Figure 1). 1 In rat and monkey PET measurements, pre‐administration of unlabeled MTP38 blocked radioactivity uptake in the brain, supporting the saturable binding of [ 11 C]MTP38 1 . In a first‐in‐human PET study of [ 11 C]MTP38, PET results showed relatively high retentions in several brain regions, including the striatum, globus pallidus, and thalamus, and rapid washout from the cerebellar cortex, corroborating the known distribution of PDE7 2 .…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…We recently developed 11 C‐labeled MTP38 ([ 11 C]MTP38) as a positron emission tomography (PET) tracer for the imaging of PDE7 (Figure 1). 1 In rat and monkey PET measurements, pre‐administration of unlabeled MTP38 blocked radioactivity uptake in the brain, supporting the saturable binding of [ 11 C]MTP38 1 . In a first‐in‐human PET study of [ 11 C]MTP38, PET results showed relatively high retentions in several brain regions, including the striatum, globus pallidus, and thalamus, and rapid washout from the cerebellar cortex, corroborating the known distribution of PDE7 2 .…”
Section: Introductionmentioning
confidence: 62%
“…Herein, 8‐amino‐3‐(2 S ,5 R ‐dimethyl‐1‐piperidyl)‐[1,2,4]triazolo[4,3‐ a ]pyrazine‐5‐carbonitrile (MTP38) was developed as a phosphodiesterase 7 (PDE7) ligand by Mitsubishi Tanabe Pharma Corporation (Osaka, Japan) and Ube Industries, Ltd (Tokyo, Japan). MTP38 potently exerted inhibitory effects on PDE7A and PDE7B with IC 50 values (nM) of 9.81 and 1.21, respectively, and showed selective affinity for other PDEs (IC 50 > 100 nM) 1 . We recently developed 11 C‐labeled MTP38 ([ 11 C]MTP38) as a positron emission tomography (PET) tracer for the imaging of PDE7 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations